Enzyme-Histochemical Demonstration of Intralobular Lymphatic Vessels in the Mouse Thymus - KATO, Seiji (Archives of Histology and Cytology, 1990)
Intralobular lymphatic vessels in the mouse thymus were demonstrated enzyme-histochemically by combined light and electron microscopy. In sections reacting to both 5′-nucleotidase (5′-Nase) and alkaline phosphatase (ALPase), the intralobular lymphatic vessels were identified as irregularly shaped spaces with strong 5′-Nase activity. The lymphatic vessels were closely associated with the branches of ALPase-positive intralobular arteries and veins. The initial lymphatics, which presumably originate from the perivascular spaces, were 5′-Nase positive. The distribution and intensity of the 5′-Nase activity in the lymphatic vessels revealed by light microscopy correlated well with those by backscattered image electron microscopy. The backscattered image scanning electron microscopy of the same area as observed under a light microscope more clearly highlighted the peculiar contours of lymphatic endothelial cells. Transmission electron microscopy showed that specific reaction product of the 5′-Nase after incubation in a medium containing L-tetramisole was predominantly localized on the outer surface of the lymphatic endothelial cell membranes.